(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
In the text referring to sexuality, the focus is on determining theoretical strategies in anthropological research, in which, in the center of researcher attention is the local system of sex/genderness in the Roma community in Skopje. Although anthropology is a discipline that offers a wide range of opportunities for theoretical solutions, with all its strengths and weaknesses, we will try, in a summarized form, to give theoretical guidance as possible design.